Neurocognitive function in procedures correcting severe aortic valve stenosis: patterns and determinants - Ranucci, L.; Brischigiaro, L.; Mazzotta, V.; Anguissola, M.; Menicanti, L.; Bedogni, F.; Ranucci, M. (Frontiers in Cardiovascular Medicine, 2024)
Background: Neurocognitive changes after surgical (SVAR) or transcatheter TAVI) procedures for the correction of severe aortic stenosis (AS) has not been widely addressed, with conflicting results. The purpose of this study is to identify the preprocedural neurocognitive pattern and its determinants in the setting of elderly (>65 years) patients with severe AS undergoing SAVR or TAVI, and its changes and determinants at 2-3 month follow-up Methods: Prospective cohort study within the Italian Registry on Outcomes in Aortic Stenosis treatment in the Elderly Patients. Patients were assessed before and after (2-3 month) the procedure using the Montreal Cognitive Assessment (MoCA) test. Periprocedural demographics, clinical factors and outcome measures were collected. Results: Before the procedure 70% of the patients demonstrated a MoCA score < 23 points, indicative of cognitive dysfunction. Factors associated with neurocognitive dysfunction were age, functional capacity, chronic heart failure and hemoglobin levels.After the procedure there was an overall improvement of the MoCA score, but 28% of the patients showed a reliable worsening. Factors associated with MoCA worsening were platelet transfusions and the amount of red blood cells units transfused.The correction of severe AS leads to an improvement in neurocognitive function after 2-3 months. This improvement does not differ between SAVR or TAVI after matching for pre-procedural factors. The only modifiable factor associated with the preprocedural neurocognitive function is anemia, and anemia correction with red blood cell transfusions is associated with a worsening of neurocognitive function. This raises the hypothesis that anemia correction before the procedure (with iron and/or erythropoietin may limit the risk of post-procedural worsening of neurocognitive function.